A NOTE ON FUZZY FUNCTION ON THE BASIS OF REFERENCE - Basumatary, Bhimraj (Journal of Global Research in Mathematical Archives(JGRMA), 2018)
The main purpose of this article is to revisit the fuzzy function with the help of extended definition of fuzzy sets. In this work, we try to give some fundamental definition of fuzzy function and try to prove some theorems on fuzzy function with the help of new definition of complement of fuzzy sets on the basis of reference function. Also, with the help of extended definition of fuzzy set we shall prove some nice theorems of fuzzy topology. Keywords- Fuzzy membership function, fuzzy reference function, fuzzy membership value, Image and preimage, fuzzy topology, fuzzy open set, fuzzy closed set, fuzzy topology, fuzzy continuous.